Clorpromazina: um remédio de seu tempo - Porto, José Eduardo Sant’Anna (2018)
Having been introduced into mental disorders’ therapeutics in 1952, chlorpromazine is not only widely considered the first of modern times’ psychotropic drugs, but the very starting point of a new science called psychopharmacology, then turning into the basis of a brand new biological psychiatry, mostly developed in twentieth century’s last quartile period. This new biological psychiatry, settled on molecular biology’s developments on synaptic neurotransmission, is actually contemporary psychiatry’s main scientific model, a framework which is kept very well and alive despite the criticism aimed at its supposed lack of theoretical foundation. Similarly, chlorpromazine’s historiography has been homogeneous with regard to the assertion that, in mid-twentieth century, there were no theoretical assumptions that could justify its introduction into the treatment of mental illness. However, research on chlorpromazine’s historical documents – mainly the scientific studies carried out at Sainte-Anne Hospital in Paris - clearly shows that its authors’ interests were closely related to the long-awaited, and then finally achieved, treatment methods, that had been celebrated as a new "therapeutic era" for psychiatry, by the way, one of the most discussed topics in the First World Congress of Psychiatry, an event that took place in 1950, two years before chlorpromazine’s introduction. Psychiatry was under a promising and cheerful atmosphere, deriving from the then recent achievements of modern therapeutic advances, which not only had justified the organization of the international congress, but also the foundation, in the same context, of the World Psychiatric Association, and the election of Jean Delay as its first president. In fact, Delay was not only one of the so commemorated therapeutic methods’ greatest theorists, but also chlorpromazine’s principal introducer, under the very same theoretical assumptions. Our study seeks to investigate the connections between all these historical events, aiming to find coherence between the scientific concepts in which they had been established, and their anchoring in the medical theories of their time. We conclude that psychiatry’s theories justifying chlorpromazine’s use in mental disease’s treatment not only retain a remarkable internal coherence, but also are broadly reunited with medical scientific precepts of their time